Improvement of students’ learning outcome in primary schools using examples non-examples learning model - Paskalis Danan Nostra Chrisandi; Henny Dewi Koeswati (Universitas Pendidikan Ganesha, 2019)
This study aims to determine the increase in students’ learning outcomes in primary schools. This type of research is Classroom Action Research (CAR) which refers to the theory of Kemmis and Mc Taggart. PTK uses 4 stages, namely planning, action and observation, and reflection. PTK is carried out through 2 cycles where 3 cycles are held in each cycle. Problem solving solutions with examples non examples learning models. The results of the study were obtained from 27 fifth grade students of SD N Pasekan 03 Ambarawa. Data collection techniques are tests and ratting skills or scale skills. Data analysis is done by statistical statistics or descriptive statistics. Complete pre-cycle learning is 10 students with a percentage reaching 37.04% and those that are not complete there are 17 students with a presentation of 62.96%. Cycle 1 which has reached the completeness limit of 13 students with a percentage of 48.15% and 14 students who have not finished with a percentage of 51.85%. Cycle II the percentage of completeness reached 81.48% with a number of 22 students who had completed and 5 students who had not finished with a percentage of 18.52%. Based on the results of the study, it was found that there was an increase in the learning outcomes of class V students in theme 8 of sub-theme 1 learning 1 and 2 using examples non examples learning models.